2007
DOI: 10.1534/genetics.106.062729
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Selection 2: Estimating the Genetic Parameters Determining Inheritance and Response to Selection

Abstract: Interactions among individuals are universal, both in animals and in plants and in natural as well as domestic populations. Understanding the consequences of these interactions for the evolution of populations by either natural or artificial selection requires knowledge of the heritable components underlying them. Here we present statistical methodology to estimate the genetic parameters determining response to multilevel selection of traits affected by interactions among individuals in general populations. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
294
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(306 citation statements)
references
References 46 publications
10
294
2
Order By: Relevance
“…Quantitative genetic models for pig growth can be modified allowing pigs to have heritable influences on the growth of their pen-mates (Bijma et al, 2007a and2007b;Rodenburg et al, 2010). Depending on the context, these 'social breeding values' might reflect differences in positive social behaviours such as social nosing (Camerlink et al, 2012) or in negative behaviours such as aggression, food competition, disease transmission and ear, flank or tail biting.…”
Section: Controlling Tail Biting Without Tail Dockingmentioning
confidence: 99%
“…Quantitative genetic models for pig growth can be modified allowing pigs to have heritable influences on the growth of their pen-mates (Bijma et al, 2007a and2007b;Rodenburg et al, 2010). Depending on the context, these 'social breeding values' might reflect differences in positive social behaviours such as social nosing (Camerlink et al, 2012) or in negative behaviours such as aggression, food competition, disease transmission and ear, flank or tail biting.…”
Section: Controlling Tail Biting Without Tail Dockingmentioning
confidence: 99%
“…Bijma et al (2007b) showed that non-genetic covariance among group mates can bias the estimates of genetic associative effects. Although we modelled social interactions differently, we fitted a random group effect to asses the magnitude of such non-genetic covariance in our analysis (see Bergsma et al 2008).…”
Section: Social Interactionsmentioning
confidence: 99%
“…However, his work had limited impact because it lacks an approach to the problem of identifying heritable components and an implementation in the framework of mixed model equations. The last has been achieved mainly by B. Muir and P. Bijama in several very elegant papers (Bijma et al, 2007a and2007b;Ellen et al, 2007;Bijma and Wade, 2008).…”
Section: Selection For Social Traitsmentioning
confidence: 99%
“…The methodology presented above has been recently applied to analyse mortality in a commercial population of layer chickens (Bijma et al, 2007b;Ellen et al, 2008). The data were provided by Hendrix Genetics and consisted of observations on survival days of a single generation of 3800 hens bred from 36 sires and 287 dams, which had been mated at random.…”
Section: Selection For Social Traitsmentioning
confidence: 99%